Development and validation of a nomogram to predict the risk of occult cervical lymph node metastases in cN0 squamous cell carcinoma of the tongue. Issue 10 (December 2019) - Jiang, Q.; Tang, A.; Long, S.; Qi, Q.; Song, C.; Xin, Y.; Zhang, C.; Cao, Z.; Zhang, J.
Abstract: We have explored the relations between clinicopathological features and cervical lymph node metastases (LNM) in patients with cN0 squamous cell carcinoma (SCC) of the tongue, and developed and validated a nomogram for predicting the risk of their development. Clinical data on 230 patients with cN0 SCC of the tongue who had had primary extended excision and lymph node dissection of the neck were collected retrospectively. They were divided into a development cohort and a validation cohort in a 4:1 ratio. Logistic regression analysis was used to assess the risk factors of cervical LNM in patients in the development cohort, and a nomogram was established to predict the risk of such nodes. In the validation cohort, the predictive performance and compliance of the model were evaluated using the consistency index (C-index) and calibration curve, and the clinical value was evaluated by decision curve analysis. Of the 230 patients, 60 had cervical LNM, of which 60 were invaded (26%). Analysis of the development cohort showed that the site of the primary lesion, depth of invasion, size of the tumour, and histopathological grade were included in the prediction model, which was validated in the validation cohort. Consistency was high (C-index = 0.846), calibration good, and it was clinically valuable. The nomogram could be used to predict the probability of occult cervical LNM before operation in patients with stage cN0 SCC of the tongue. It could also be used as a reference tool for dissection of cervical nodes and a communication tool between the doctor and the patient.